Pengembangan Modul Pendidikan Agama Islam Materi Kisah Berbasis Gambar pada Peserta Didik Kelas V SD Inpres Mangga Tiga Kota Makassar - Alfatiha Nur A. Fatima Kedang; A. Marjuni; Rosdiana (Jurnal Pendidikan Kreatif, 2024)
This research focuses on developing Islamic Religious Education Modules based on illustrated stories for fifth-grade students at SD Inpres Mangga Tiga, Makassar. The main questions addressed in this study are: 1) How is the development of Islamic Religious Education Modules based on story illustrations for fifth-grade students at SD Inpres Mangga Tiga, Makassar described? 2) What is the validity level of the developed module? 3) How effective is the developed module in improving learning outcomes? The research utilizes a research and development (R&D) approach, employing the 4D model by Thiagarajan and Semmel, which includes defining, designing, developing, and disseminating. The study involved three key stages: defining the needs and objectives, designing the module, and developing it, followed by validation by experts and piloting with students. The findings indicated that the module achieved high validity, with a mean score of 4.916, and proved effective in enhancing learning outcomes, demonstrated by a learning completeness rate of 94.11% and a positive response from students, which was 97.64%. The implications of this study suggest that careful analysis and rigorous validation are crucial during the module development process to ensure the production of high-quality educational materials. This approach not only validates the content but also ensures the effectiveness and receptiveness of the educational tools among students, thereby enhancing their learning experiences and outcomes.